Emerging roles for IL-25 and IL-33 in colorectal cancer tumorigenesis - Jou, Eric; Rodriguez-Rodriguez, Noe; McKenzie, Andrew N. J. (Frontiers in Immunology, 2022)
Colorectal cancer (CRC) is the second leading cause of cancer-related death worldwide, and is largely refractory to current immunotherapeutic interventions. The lack of efficacy of existing cancer immunotherapies in CRC reflects the complex nature of the unique intestinal immune environment, which serves to maintain barrier integrity against pathogens and harmful environmental stimuli while sustaining host-microbe symbiosis during homeostasis. With their expression by barrier epithelial cells, the cytokines interleukin-25 (IL-25) and IL-33 play key roles in intestinal immune responses, and have been associated with inappropriate allergic reactions, autoimmune diseases and cancer pathology. Studies in the past decade have begun to uncover the important roles of IL-25 and IL-33 in shaping the CRC tumour immune microenvironment, where they may promote or inhibit tumorigenesis depending on the specific CRC subtype. Notably, both IL-25 and IL-33 have been shown to act on group 2 innate lymphoid cells (ILC2s), but can also stimulate an array of other innate and adaptive immune cell types. Though sometimes their functions can overlap they can also produce distinct phenotypes dependent on the differential distribution of their receptor expression. Furthermore, both IL-25 and IL-33 modulates pathway previously known to contribute to CRC tumorigenesis, including angiogenesis, tumour stemness, invasion and metastasis. Here, we review our current understanding of IL-25 and IL-33 in CRC tumorigenesis, with specific focus on dissecting their individual function in the context of distinct subtypes of CRC, and the potential prospects of targeting these pathways in CRC immunotherapy.